(untitled) (Research, Society and Development, 2021)
Objective: To identify the levels of evidence from studies related to anxiety, stress and depression among nursing professionals. Method: integrative literature review, carried out in LILACS, BVSENF and SCIELO databases / databases, between 2015 and 2019, with the descriptors: nursing, anxiety, stress and depression. To carry out the bibliographic search, the PICO strategy was adopted, to select and evaluate the articles, the strategy recommended by the PRISMA group was used. To verify the level of evidence of the studies, the instrument recommended by Gershon and collaborators (1999) was used. Results: 525 articles were found, of which only 17 met the inclusion criteria. Of the selected articles, most were published between 2018 and 2019 (53%). Of these, a large part has a descriptive and quantitative study design (47%). It is noteworthy that only 30% of the studies were carried out in university hospitals and the majority in the public network. Most studies sought evidence of stress in the work environment of nursing professionals (94%). Only 29% of studies investigated anxiety and 17% depression. It was found that the studies presented weak levels of evidence, since all of them had a descriptive approach, considered as level 6 of evidence. Conclusion: It became evident that nursing professionals suffer recurrently from anxiety, stress and depression in hospital environments. However, studies have a low level of evidence, pointing to the need for further investigations with studies that present stronger evidence.